General theory of employment interest and money - "Keynes, John Maynard" (London, 1949)
John Maynard Keynes is the great British economist of the twentieth century whose hugely influential work The General Theory of Employment, Interest and Money is undoubtedly the centuryandrsquo;s most important book on economicsandmdash;strongly influencing economic theory and practice, particularly with regard to the role of government in stimulating and regulating a nationandrsquo;s economic life. Keynesandrsquo;s work has undergone significant revaluation in recent years and andldquo;Keynesianandrdquo; views which have been widely defended for so long are now perceived as at odds with Keynesandrsquo;s own thinking. Recent scholarship and research has demonstrated considerable rivalry and controversy concerning the proper interpretation of Keynesandrsquo;s works, such that recourse to the original text is all the more important. Although considered by a few critics that the sentence structures of the book are quite incomprehensible and almost unbearable to read, the book is an essential reading for all those who desire a basic education in economics. The key to understanding Keynes is the notion that at particular times in the business cycle, an economy can become over-productive (or under-consumptive) and thus, a vicious spiral is begun that results in massive layoffs and cuts in production as businesses attempt to equilibrate aggregate supply and demand. Thus, full employment is only one of many or multiple macro equilibria. If an economy reaches an underemployment equilibrium, something is necessary to boost or stimulate demand to produce full employment. This something could be business investment but because of the logic and individualist nature of investment decisions, it is unlikely to rapidly restore full employment. Keynes logically seizes upon the public budget and government expenditures as the quickest way to restore full employment. Borrowing the money to finance the deficit from private households and businesses is a quick, direct way to restore full employment while at the same time, redirecting or siphoning off the funds from the private sector which caused the over-production is in the first place. Keynesandrsquo;s theory is unquestionably significant in understanding of modern economics. Far from being destructive, it alone has been responsible for nearly 60 years of growth without a major depression as we experienced worldwide in the 1930s.While the present book is indispensable for the students, researchers and teachers of Economics, it is highly useful for the general readers keenly interested in understanding nationandrsquo;s economy.
Keywords: Economics